Violations of Human Rights during the Period of ISIS Control in Iraq - Faisal Abdullah, Assist. Lect. Israa (Basra studies journal, 2026)
Human rights constitute one of the fundamental pillars upon which contemporary international legal systems are based. However, the terrorist organization ISIS committed widespread and systematic violations of these rights in Iraq during its period of territorial expansion. This research aims to examine the crimes committed by the organization, with a particular focus on genocide and crimes against humanity targeting religious and ethnic minorities such as Yazidis, Christians, and Turkmen, in addition to serious abuses against women and children. The study adopts both analytical and descriptive methodologies: the analytical approach is used to examine relevant international legal instruments, while the descriptive approach is employed to document the principal crimes and incidents. The first part of the study addresses the nature of ISIS and its major crimes, while the second part examines the role of the International Criminal Court and the Iraqi Central Criminal Court specialized in terrorism cases in addressing these violations. The study concludes that the crimes committed by ISIS meet the legal threshold of international crimes, requiring prosecution at both national and international levels, with an emphasis on strengthening the Iraqi judiciary and enhancing international cooperation to ensure justice for victims.